2006
DOI: 10.1194/jlr.m600215-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The age-related paraoxonase 1 response is altered by long-term caloric restriction in male and female rats

Abstract: Caloric restriction (CR) has been shown to attenuate age-related oxidative damage and to improve major atherosclerotic risk factors. Paraoxonase 1 (PON1), an enzyme specifically associated with HDL containing apolipoproteins A-I and J, has been reported to prevent the proatherosclerotic effects of oxidized LDL. The aim of this study was to evaluate whether modulation of PON1 activity is part of the underlying CR mechanisms that attenuate the ageassociated negative effects. Experimental groups were 1 year old r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…As a whole, these results point to a greater oxidative status in the organism that, in part, would result from impaired antioxidant capacity. Although the antioxidant role of PON1 has recently been called into question (43), the present results and others previously described in different physiological situations characterized by changes in the oxidative status (18,19,20,44), suggest that this enzyme would be involved in the response to oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…As a whole, these results point to a greater oxidative status in the organism that, in part, would result from impaired antioxidant capacity. Although the antioxidant role of PON1 has recently been called into question (43), the present results and others previously described in different physiological situations characterized by changes in the oxidative status (18,19,20,44), suggest that this enzyme would be involved in the response to oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
“…These gender differences in both PON1 activity and stability have been previously reported in younger rats (18). However, the inversion of gender differences in serum PON1 activity observed with aging (20) is not yet obvious at 18 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we previously reported, the decreased serum PON1 activity induced by caloric restriction was a direct consequence of a lower number of PON1 molecules in the blood as a result of the reduced HDL content of apoA-I and apoJ, leading to a loss of stability in the PON1-HDL complexes and/or to lower levels of the HDL subfraction to which PON1 associates [39,40]. However, the mechanisms involved in the changes in PON1 activity during fasting are different from those operating during caloric restriction and cannot be attributed either to changes in apoA-I, apoJ or PON1 serum levels.…”
Section: Kdamentioning
confidence: 69%
“…Paraoxonase and ARE activities have different patterns in response to DR. Long‐term DR decreased testicular ARE activities significantly in both temperatures ( P < 0.05), while it did not change PON activity significantly in this study. This discrepancy between PON and ARE may be due to differences in the specific regulation of both enzymes (Thomas‐Moya et al ., ). It has been reported that the effect of DR depends on many variables such as age and duration and degree of restriction (Gredilla et al ., ).…”
Section: Discussionmentioning
confidence: 97%